Sarcoidosis: histopathological definition and clinical diagnosis. - Mitchell, D N (1977)
Sarcoidosis is best defined in histopathological terms as 'a disease characterised by the presence in all of several affected organs and tissues of non-caseating epithelioid-cell granulomas, proceeding either to resolution or to conversion into hyaline connective tissue'. Although the defining characteristics are thus histopathological, diagnosis during life depends largely upon clinical, radiological, and immunological findings. The amount of support required from histology varies greatly from case to case. Though histology from one site cannot in itself establish the diagnosis of sarcoidosis, a generalised disease, detailed histological study of biopsy tissue makes an important and often essential contribution. In many instances, complete lack of necrosis, an intact reticulin pattern, and failure to demonstrate infective agents permit an unequivocal statement of compatibility with this diagnosis; however, a compatible clinical picture and absence of evidence of known causes of local granulomatous reactions or of other generalised granulomatous diseases are required for definitive diagnosis. In some, the histological pattern deviates in some particular from the accepted 'typical' pattern; there may be a little necrosis, the follicular pattern of the granuloma may be less than perfect, and exclusion of known infective agents can never be absolute. In such instances, subsequent surveillance, including possible response to treatment, may show a clinical course justifying a diagnosis of sarcoidosis, and necropsy may establish it; but it must be recognised that in a few cases, particularly those in which the clinical evidence of disease is confined to one organ, diagnosis is likely to remain in doubt for long periods. Reports on the histology of the Kveim test should be made without knowledge of clinical findings and in terms of the presence and quality of granulomatous response. A granulomatous reaction to a validated test suspension makes a contribution to diagnosis similar to the finding of granulomas in an additional organ or tissue.